Intergrated approach against Striga - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2012)
The parasitic weed striga causes more damage to cereal crops in poor soils, so both problems have to be tackled together. In this video we will learn why it is important to combine at least three control methods to reduce striga and obtain a good yield of sorghum, millet, maize or rice.